Features of ecology for bivalve mollusk Potamocorbula amurensis in Peter the Great Bay, Japan Sea - E. V. Kolpakov; D. D. Nemova; D. A. Sokolenko (Известия ТИНРО, 2024)
Features of ecology are considered for euryhaline bivalve mollusk Potamocorbula amurensis dwelling in Peter the Great Bay. Spatial distribution of the species is not uniform, the mollusks settle mainly in the areas affected to the river discharge influence with water salinity from 5 to 30 ‰, in the uppermost layer of silty, silt-sandy, sandy, sandy-gravely, or sandy-gravel-pebbly soils at the depths from 0.3 to 7.0 m. The densest aggregations of P.amurensis are found in the top of Amur Bay, with the biomass up to 2.3 kg/m2 and abundance > 31.103 ind./m2 at the depths shallower 2.0 m. They are able to form a byssus thread up to 30 mm long. This sestonophag species occupies usually a dominant or subdominant position in benthic communities, and itself is a prey for asian paddle crab Charybdis japonica and seabirds. Larvae of P. amurensis could be transported by estuarine streams to estuaries and lagoons where the species forms temporary aggregations dependent on the parental stocks, but in the vast Razdolnaya River estuary, especially in the relatively deep Tavrichansky Liman, there are stable mixed-age settlements where the specimens of age 5+ can be found that is the maximum life span of P. amurensis for Peter the Great Bay.